Swarm leadership and the collective mind using collaborative innovation networks to build a better business - Gloor, Peter A. 1961- (Emerald Publishing Limited, 2017)
This book helps you to become the leader of your own swarm by building its collective consciousness. A successful swarm business channels the competitive energies of all stakeholders towards collaboration. The journey from homo competitivus to homo collaborensis starts with recruiting and building an intrinsically motivated group of early enthusiasts, the Collaborative Innovation Network. These teams of homo collaborensis combine the four principles of social quantum physics to create collective consciousness: empathy that builds entanglement, and reflection that leads to personal reboot and refocus. Once the team is operational, its collaboration can be tracked and boosted using the "six honest signals of collaboration", patterns of collaboration, which will further increase the performance of the swarm. The six honest signals are central leadership, rotating leadership, balanced contribution, responsiveness, honest sentiment, and shared context. These concepts are illustrated with examples from leading organizations based on decades of research by the author at MIT, ranging from the creation of the Web, Uber and Airbnb to Fortune 500 high tech firms and healthcare organizations
Keywords: Business & Economics; Management: leadership & motivation; Social sciences and management; Soziales Netzwerk; Führung